Using Wikis for Online Group Projects: Student and Tutor Perspectives - Kear, Karen; Donelan, Helen; Williams, Judith (International Review of Research in Open and Distributed Learning, 2014)
This paper presents a study of the use of wikis to support online group projects in two courses at the UK Open University. The research aimed to investigate the effectiveness of a wiki in supporting (i) student collaboration and (ii) tutors’ marking of the students’ collaborative work. The paper uses the main factors previously identified by the technology acceptance model (TAM) as a starting point to examine and discuss the experiences of these two very different user groups: students and tutors. Data was gathered from students via a survey and from tutors via a range of methods. The findings suggest that, when used in tandem with an online forum, the wiki was a valuable tool for groups of students developing a shared resource. As previous studies using the TAM have shown, usefulness and ease of use were both important to students’ acceptance of the wiki. However, the use of a wiki in this context was less well-received by tutors, because it led to an increase in their workload in assessing the quality of students’ collaborative processes. It was possible to reduce the tutor workload by introducing a greater degree of structure in the students’ tasks. We conclude that when introducing collaborative technologies to support assessed group projects, the perceptions and needs of both students and tutors should be carefully considered.